Analisis Parameter Spesifik Dan Non Spesifik Simplisia Daun Cengkeh (Syzygium aromaticum L.) - Balqis Tamatantri, Amani; Mulatasih, Endah (Universitas Bhakti Kencana, 2025)
The leaves of the clove plant (Syzygium aromaticum L.) have not been optimally utilized despite containing active compounds such as flavonoids, triterpenoids, phenolics, and tannins with potential antibacterial properties. This study aims to evaluate the quality of clove leaf simplicia through specific and non-specific parameter analysis as a basis for establishing pharmaceutical raw material standards. The research employed a non-experimental design with a descriptive- analytical approach. Specific parameters assessed included simplicia identification, organoleptic characteristics, microscopic analysis, and water- and ethanol-soluble extract content. Non-specific parameters covered drying loss, moisture content, total ash, and acid-insoluble ash. The results showed that the simplicia powder had a green color, a distinct aroma, a bitter taste, and contained active compounds such as saponins, tannins, alkaloids, flavonoids, and steroids. The water-soluble extract content was 25.569%, and the ethanol-soluble extract content was 14.106%. Meanwhile, the non-specific test results indicated a drying loss of 8.8%, moisture content of 10.23%, total ash content of 3.87%, and acid-insoluble ash content of 0.85%. Based on these findings, clove leaf simplicia meets quality standards and has potential for use as a raw material in traditional medicine formulations